Metabolic Engineering of Pseudomonas putida KT2440 to Produce Anthranilate from Glucose - Kuepper, Jannis; Dickler, Jasmin; Biggel, Michael; Behnken, Swantje; Jäger, Gernot; Wierckx, Nick; Blank, Lars M. (Frontiers in Microbiology, 2015)
The Pseudomonas putida KT2440 strain was engineered in order to produce anthranilate (oAB, ortho-aminobenzoate), a precursor of the aromatic amino acid tryptophan, from glucose as sole carbon source. To enable the production of the metabolic intermediate oAB, the trpDC operon encoding an anthranilate phosphoribosyltransferase (TrpD) and an indole-3-glycerol phosphate synthase (TrpC), were deleted. In addition, the chorismate mutase (pheA) responsible for the conversion of chorismate over prephenate to phenylpyruvate was deleted in the background of the deletion of trpDC to circumvent a potential drain of precursor. To further increase the oAB production, a feedback insensitive version of 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase encoded by the aroGD146N gene and an anthranilate synthase (trpES40FG) were overexpressed separately and simultaneously in the deletion mutants. With optimized production conditions in a tryptophan-limited fed-batch process a maximum of 1.54 ± 0.3 g L-1 (11.23 mM) oAB was obtained with the best performing engineered P. putida KT2440 strain (P. putida ΔtrpDC pSEVA234_aroGD146N_trpES40FG).